2017
DOI: 10.18632/oncotarget.23784
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 induces adenosine receptor A2a and promotes human squamous carcinoma cell growth via extracellular signal regulated kinases ½

Abstract: Patient treatment for oral squamous cell carcinoma (OSCC) not associated with Human papillomavirus remains problematic. OSCC microenvironment is typically inflamed and colonized by microorganisms, providing ligands for toll-like receptors (TLR). In immune cells TLR2 and TLR4 activate NF-kB and extracellular signal regulated kinase (ERK)1/2 pathways, leading to upregulation of inhibitory adenosine receptors A2a and A2b, and reduction in stimulatory A1 and A3. How TLR and adenosine receptors function in SCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…While other studies have demonstrated the functional role of IL-1 and signaling pathway of TLR4 in astrocytes 51,52 , to our knowledge, this is the first time the critical autocrine/paracrine effects of TNF-α on astrocyte functioning are demonstrated. In addition, other studies have demonstrated the roles of TLRs, including TLR2 and TLR4, in upregulating proliferation in various cancers [53][54][55][56] , to our knowledge, we are the first to demonstrate their significance in the transition between quiescent and proliferative astrocytes via the production of TNF-α. Our findings will likely delineate the cellular and molecular mechanisms involved in different neurological conditions.…”
Section: Discussionmentioning
confidence: 68%
“…While other studies have demonstrated the functional role of IL-1 and signaling pathway of TLR4 in astrocytes 51,52 , to our knowledge, this is the first time the critical autocrine/paracrine effects of TNF-α on astrocyte functioning are demonstrated. In addition, other studies have demonstrated the roles of TLRs, including TLR2 and TLR4, in upregulating proliferation in various cancers [53][54][55][56] , to our knowledge, we are the first to demonstrate their significance in the transition between quiescent and proliferative astrocytes via the production of TNF-α. Our findings will likely delineate the cellular and molecular mechanisms involved in different neurological conditions.…”
Section: Discussionmentioning
confidence: 68%
“…IHC was done as previously described . Briefly, 5 µm sections of formalin‐fixed paraffin‐embedded tissue were de‐paraffinized and rehydrated with ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…IHC was done as previously described. 19 Briefly, 5 µm sections of formalin-fixed paraffin-embedded tissue were deparaffinized and rehydrated with ethanol. Antigen retrieval was done in water bath heating at 97°C with citrate buffer PH6 (Thermofisher).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…[1][2][3][4][5] TLR2 promotes multiple cancers though the TLR2/MYD88 innate immune signal transduction adaptor (MyD88)/tumor necrosis factor (TNF) receptor associated factor 6 (TRAF66)/Jun proto-oncogene (Jun)/p38 MARK (p38)/mitogen-activated protein kinase (MAPK) (TLR2/MyD88/TRAF6/Jun/p38/MAPK) pathways. [6][7][8][9] The current study explored the ability of miR-144-5p to target TLR2 in glioblastoma cells after GS-Rd was administration. miR-144-5p was down-regulated in 4 types of glioblastoma cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The up-regulation of Toll-like receptor 2 (TLR2) is involved in the progression, migration, and poor clinical diagnosis of various cancers through multiple pathways. [6][7][8][9] In previous studies, TLR2 was validated as a target of miR-144-5p, and the expression of TLR2 can be inhibited by the overexpression of miR-144-5p. 10,11) Ginsenoside Rd (GS-Rd) has shown strong anti-tumor activity through inhibiting epidermal growth factor receptor (EGFR) signaling, oxidative stress, and protein kinase B (Akt)/mammarian target of rapamycin kinase (mTOR)/ ribosomal protein S6 kinase (p70S6K) (Akt/mTOR/p70S6K) signaling in various cancers.…”
Section: Introductionmentioning
confidence: 99%